Parametric Analysis of CANDU Neutron Transients - McCormick, T.R. (My University, 1981)
A fundamental and important part of nuclear reactor development and analysis today is the study of neutronics following a breach in the primary heat transport circuit. In the past, much of this analysis has concentrated on the calculation of the thermalhydraulic changes which occur following a loss of coolant accident and the effects these subsequently have on neutron kinetics. The purpose of this present study is to examine the influence of neutronic parameters on the size and shape of power pulses which result from loss of coolant accidents. The parameters studied are shutdown system delay times, shutoff rod drop curves, and fuel burnup distribution.
PART B
One of two project reports: The other part is designated as Part A
Keywords: CANDU; Neutron Transients; Parametric Analysis; nuclear reactor